DEVELOPMENT OF SPECIAL PROPERTY RIGHTS REGIMES - Midorović, Sloboda D; Nikolić, Dušan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
In recent years, the shaping of special legal regimes has been intensified. They discreetly influence the ideological and value orientation of the Civil law and, to an increasing extent, its structure. Deviation from the general legal regime means that individuals or narrower social groups are brought either to a privileged or to a less favorable position in relation to other right holders. A more pronounced disparity between the general and the special can affect the stability of society, especially when it comes to the segment of the legal system that regulates issues related to the distribution and appropriation of goods in the domain of Real property law and Inheritance law. The introduction of new special legal regimes should affect the spread of Civil law. However, in most legal systems there is an opposite trend. New legal institutes that are in the function of implementing special legal regimes are governed by special regulations and often become part of separate, independent branches of law. Dispersion is especially emphasized in the domain of Real property law.The problem is that special legal regimes have not been the subject of more detailed studies in domestic doctrine. In this paper, questions concerning their conceptual definition, legal nature and practical significance are opened. In the first part, which could be conditionally called general, the current problems related to ideological and systemic dilemmas are analyzed. In the second, special, the current concept of a special property regime that applies to cultural goods is analyzed.Cultural goods are material elements of the cultural heritage of our country. The Constitution of the Republic of Serbia recognizes their status as goods of public interest, which implies the need for their enhanced protection. It is achieved by prescribing various public law restrictions that narrow the autonomy of the will of the owner. The paper analyzes the limitations of property entitlements for immovable and movable cultural goods, as well as for the goods that enjoy prior protection. Domestic regulations are inadequate in some segments because they provide for excessive restrictions (e.g. when determining the category of goods to which the right of pre-emption applies), because in some places they are insufficiently precise (in terms of determining the holder of the pre-emption right), or insufficiently elaborated (due to the failure to provide for the notification (die Anmerkung) of an (immovable) property that enjoys prior protection in the real estate cadastre). This emphasizes the importance of striving to achieve a fair balance between the public interest of the community, on the one hand, and the interests of owners, on the other.
Keywords: special legal regime; legal policy; real right; cultural goods